The economics of cowpea seed contracting in Ghana - Martey, E.; Etwire, P.M.; Owusu, E.Y.; Adogoba, D.S.; Haruna, B.; Suraj, M.M.; Omoigui, L. (Informa UK Limited, 2025)
The economic impact of agricultural contracting in developing economies has been widely studied. However, limited attention has been given to the specific dynamics of seed contracting among seed producers, despite their crucial role in seed delivery systems. Price volatility remains a significant challenge in agricultural production, often leading to low farmer incomes. Additionally, inconsistent access to agricultural inputs aligned with production calendars exacerbates productivity losses. Seed contracting can act as a mechanism to ensure guaranteed prices, reduce price volatility, and mitigate market risks for farmers. This study utilizes farm-level data and a two-stage least squares (2SLS) instrumental variable approach to examine the relationship between seed contracting and income among cowpea farmers in Ghana. Findings reveal that seed producers engaged in formal or informal contracts achieve higher productivity and income compared to non-contract producers. Heterogeneity analysis indicates that adult-headed households benefit more from seed contracting than youth-headed households. Moreover, producers with the highest cowpea productivity but lowest incomes gain substantially from seed contracting. These results remain robust across different estimation methods that account for endogeneity. The study underscores that rural livelihood can be improved through incentive-compatible seed contracting, which aligns the interests of both parties and minimizes spatial arbitrage.